2019
DOI: 10.18632/aging.102540
|View full text |Cite
|
Sign up to set email alerts
|

Screening, identification and validation of CCND1 and PECAM1/CD31 for predicting prognosis in renal cell carcinoma patients

Abstract: Clear cell renal cell carcinoma (ccRCC) is one of the most common cancers worldwide. Despite intense efforts to elucidate its pathogenesis, the molecular mechanisms and genetic characteristics of this cancer remain unknown. In this study, three expression profile data sets (GSE15641, GSE16441 and GSE66270) were integrated to identify candidate genes that could elucidate functional pathways in ccRCC. Expression data from 63 ccRCC tumors and 54 normal samples were pooled and analyzed. The GSE profiles shared 379… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 59 publications
3
26
1
Order By: Relevance
“…For instance, TNF-α is an independent prognostic indicator, and normal levels in plasma can highly predict the good prognosis of untreated RCC patients ( 88 , 145 ). In addition, CXCR4 has significant prognostic value in univariate analysis, and its low expression indicates a good prognosis ( 146 ). The high expression of CCR3 in immunohistochemical analysis is associated with the degree of malignancy of the tumor.…”
Section: Inflammation-associated Molecules and Clinical Prognosis In mentioning
confidence: 99%
“…For instance, TNF-α is an independent prognostic indicator, and normal levels in plasma can highly predict the good prognosis of untreated RCC patients ( 88 , 145 ). In addition, CXCR4 has significant prognostic value in univariate analysis, and its low expression indicates a good prognosis ( 146 ). The high expression of CCR3 in immunohistochemical analysis is associated with the degree of malignancy of the tumor.…”
Section: Inflammation-associated Molecules and Clinical Prognosis In mentioning
confidence: 99%
“…[10] Study has shown that in patients with ccRCC, the expression of PECAM1 is increased, which is associated with mild clinicopathological parameters, and it is significantly increased only in the early stage of the disease. [11] However, our analysis showed that PECAM1 expression was down-regulated in stage 1 patients with PRCC type I. Therefore, PECAM1 may be an early diagnostic indicator to distinguish ccRCC from PRCC.…”
Section: Microarray Technology and Bioinformatics Analysis Have Been mentioning
confidence: 61%
“…Among the host genes in our study, some had previously been identified by cancer-related institutes. For instance, PECAM1 was suggested as an independent prognostic factor in clear cell renal cell carcinoma [42]. Meanwhile, the method of studying circRNAs' host gene had been used by many studies.…”
Section: Discussionmentioning
confidence: 99%